Harga Jual BioCNG dari Palm Oil Mill Effluent sebagai Sumber Energi Alternatif - Irhan Febijanto (Jurnal Serambi Engineering, 2019)
Indonesia as the largest producer of palm oil, produces huge palm oil wastewater. The wastewater produces biogas which contributes to global warming, and the utilization of the biogas reduces GHG emissions of methane gas. By increasing the concentration of methane gas in the biogas, and increasing the gas pressure of biomethane, so-called bioCNG (Compressed Natural Gas), the gas utilization easier in the transportation and the energy content of the gas increases. In this paper, an assessment of the economics of bioCNG production facility in the Palm Oil Mill (POM) with a capacity of 60 tons/hour was conducted. The investment cost is estimated based on the biogas flow rate produced from an aerobic digester in the POM. By using a covered lagoon technology for anaerobic digester, and technology of membrane for gas purification, and based on the natural gas trading regulations, the selling price of bioCNG is determined by 10.27 USD/MMBTU with an IRR of 12%. This price can compete with the prices of other fossil fuels. However, the support from government regulations are still needed to utilize bioCNG as a new renewable fuel that can contribute to national energy security, GHG reduction, and achievement of the mix energy target.